2016
DOI: 10.1007/s12017-016-8420-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Rice Bran Extract Supplementation on Survival, Cognition and Brain Mitochondrial Function in Aged NMRI Mice

Abstract: Aging represents a major risk factor for the development of neurodegenerative diseases like Alzheimer's disease (AD). As mitochondrial dysfunction plays an important role in brain aging and occurs early in the development of AD, the prevention of mitochondrial dysfunction might help to slow brain aging and the development of neurodegenerative diseases. Rice bran extract (RBE) contains high concentrations of vitamin E congeners and γ-oryzanol. We have previously shown that RBE increased mitochondrial function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 56 publications
8
23
1
Order By: Relevance
“…Monitoring the following aging process, 18-month-old mice had a significantly reduced alternation rate and number of alternations compared to young control animals, indicating a reduced spatial learning memory and mobility in 18-month-old NMRI mice (Figures 1(a) and 1(b)) which is in agreement with previous studies [29,36]. In comparison, other studies already showed a significantly decreased performance in the Ymaze test in middle-aged mice [43,49].…”
Section: Behavioral Testingsupporting
confidence: 90%
See 2 more Smart Citations
“…Monitoring the following aging process, 18-month-old mice had a significantly reduced alternation rate and number of alternations compared to young control animals, indicating a reduced spatial learning memory and mobility in 18-month-old NMRI mice (Figures 1(a) and 1(b)) which is in agreement with previous studies [29,36]. In comparison, other studies already showed a significantly decreased performance in the Ymaze test in middle-aged mice [43,49].…”
Section: Behavioral Testingsupporting
confidence: 90%
“…Effect of Aging on Cognitive Performance. Spatial learning memory and locomotor activity were determined using the Y-maze spontaneous alternation test in 3-, 6-, 12-, and 18month-old mice [29,35,36]. Mice, aged 6 or 12 months, showed slightly but not significantly decreased changes in alternation rates compared to young controls during a five-minute testing phase (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term supplementation has a positive impact on survival, cognition and brain mitochondrial function, which may delay Alzheimer's disease [64]. Rice bran supplements can also be used as ergogenic supplements by body builders and athletes [65] and they may mitigate menopausal symptoms such as hot flashes, as well as bone loss in older women who suffer from osteoporosis [66].…”
Section: General Health-promoting Aspectsmentioning
confidence: 99%
“…Rice bran HRV induced diarrhea prevention in gnotobiotic pigs 10% ↑ Intestinal IFN-γ and total IgA levels [63] γ-Oryzanol Brain aging in NMRI mice 4 g/kg diet for 6 months ↑ Mitochondrial proteins [64] γ-Oryzanol Human health growth 500 mg/day ↑ Muscular strength (bench press and squat) and vertical jump power [65] γ-Oryzanol Postmenoposal osteoporosis in rats 0.3% crystalized oryzanol ↑ Estrogen, Bone mineral [66] HRV, human rota virus; IFN-γ, interferon gamma; IgA, immunoglobulin A. …”
Section: Health Aspects Dose Effect Refmentioning
confidence: 99%